Periglacialne in ledeniške oblike v zahodnem delu Pohorja - Obu, Jaroslav (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
Recent geomorphological research in eastern part of Pohorje Mountains has revealed new information about periglacial and glacial landforms of that area. Based on these findings, similar landforms in western part of Pohorje were studied, especially cryoplanation terraces and nivation hollows. Field research has also revealed the existence of ploughing rocks, blockstreams, blockfields and one cirque.
Keywords: geomorfologija; geomorphology; glacial geomorphology; glacial landforms; glacialna geomorfologija; ledeniški relief; periglacial landforms; periglacialni relief; Pohorje; relief; Slovenia; Slovenija; topography